Enterobiasis Masquerading as Acute Appendicitis: A Case Series from a Remote Indian Island (GAIMS Journal of Medical Sciences, 2023)
Enterobius vermicularis is a common parasitic infection and is rarely seen as an incidental finding in appendectomy specimens. Enterobius vermicularis often presents with symptoms similar to acute appendicitis. We present six cases with clinical features of acute appendicitis. Appendectomies were done for all the cases and the histopathological examination showed Enterobius vermicularis in the lumen of appendix in all six cases. Four cases showed lymphoid hyperplasia without acute inflammation, one case showed evidence of acute inflammation (acute appendicitis) and one case showed normal histology with no evidence of acute inflammation. Enterobius vermicularis infestation is quite common in India but these six cases belong to the remote Indian Islands of Andaman & Nicobar. Enterobiasis may rarely present as acute appendicitis and careful histopathological examination needs to be done for initiation of post-operative antiparasitic medications. Preoperative diagnosis of these patients is important to avoid unnecessary surgery unless presenting as a surgical emergency.